Design and Analysis of Single Motor-Driven Deployable Grasping Mechanism for Non-Cooperative Space Debris - Sajjad Manzoor; Yibo Wang; Kyungtae Kim; Qiang Lu; Youngjin Choi (IEEE Access)
In this paper, a new deployable grasping mechanism for non-cooperative space debris is proposed and developed. This grasping mechanism consists of three robotic fingers connected to a platform. Each finger is developed by combining a series of scissors mechanisms, in such a way that one mechanism drives the next. A half scissors mechanism is used at the end of finger as a its tip. These fingers are deployable and their length increases and decreases with the closing and opening of the scissors mechanism. Each deployable modules is equipped with a grasp driver mechanism, which can gradually bend the finger during the process of increase in its length, in order to accomplish the grasping of the non-cooperative space debris. Each finger is designed as an under-actuated mechanism, to save the development cost and make the finger lightweight. A special mechanism is developed in the platform of the grasping mechanism, such that single motor can be used to deploy and bend all the fingers, simultaneously. In the end, the validation of the working and effectiveness of the proposed deployable grasping mechanism is given through simulations and experimental work. It can be observed through the results that the proposed mechanism is able to grasp large objects with simultaneous deployment and bending of all fingers by using single motor.